Communicative competence of new students of the faculty of Health Sciences, University Centroccidental Lisandro Alvarado cohort 2010-1 (Revista Electrónica REDINE, 2018)
Communication is an element of the culture of each group, therefore, its expression becomes the purest expression of values and norms that guide human interaction. This exploratory study has as an aim to recognize the communicative skills of 39 students participating in the course organized by the Student Support Unit Newcomer of the Dean of Health Sciences, part of the 2010-1 cohort. The information was collected through a brief opening statement made in the virtual forum provided by SEDUCLA, which was given a textual analysis. The processing of the results was conducted through analysis of frequency, percentages, and they indicate that any act of communication among two or more people in any situation of personal exchange, in this case, work online via computer, is governed more by rules of social interaction that grammatical and linguistic dominance of the speakers.
Keywords: communicative competence; sociolinguistic dimension; grammatical and discursive